HoxC5 and miR-615-3p target newly evolved genomic regions to repress hTERT and inhibit tumorigenesis - Bi, Xuezhi (2018)
The repression of telomerase activity during cellular differentiation promotes replicative aging and functions as a physiological barrier for tumorigenesis in long-lived mammals, including humans. However, the underlying mechanisms remain largely unclear. Here we describe how miR-615-3p represses hTERT expression. mir-615-3p is located in an intron of the HOXC5 gene, a member of the highly conserved homeobox family of transcription factors controlling embryogenesis and development. Unexpectedly, we found that HoxC5 also represses hTERT expression by disrupting the long-range interaction between hTERT promoter and its distal enhancer. The 3′UTR of hTERT and its upstream enhancer region are well conserved in long-lived primates. Both mir-615-3p and HOXC5 are activated upon differentiation, which constitute a feed-forward loop that coordinates transcriptional and post-transcriptional repression of hTERT during cellular differentiation. Deregulation of HOXC5 and mir-615-3p expression may contribute to the activation of hTERT in human cancers.